Intensity of anar butterfly Virachola isocrates (Fabr.) with period and crop means - Sunita, Sunita (Recent Research in Science and Technology, 2012)
Guava is a popular fruit crop but several insect pests easily damage the crop. Guava is mainly a crop of U.P. where it is used in large amount by all classes of the society. Anar butterfly (Virachola isocrates Fabr.) is found throughout the year except May and June. Data recorded on the population of oriental fruit fly larvae in period, period x crops, months, crops and month x crops were summarized. Among the 40 periods of population of Virachola isocrates was found the highest (35.600 per unit) in 3rd week of September and it was followed by 32.219 in the 3rd week of August, 28.285 in the 2nd week of September and 27.180 in the 4th week of August, 28.285 in the 2nd week of September and 27.180 in the 4th week of December. The minimum population was observed in the 4th week of November i.e. of population 10.794 per unit, respectively. In fact this showed a great range of variation. It was very apparent that population fluctuation varied from September to November.